2011
DOI: 10.1111/j.1462-5822.2011.01704.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Psl polysaccharide reduces neutrophil phagocytosis and the oxidative response by limiting complement-mediated opsonization

Abstract: Summary Pseudomonas aeruginosa causes chronic lung infections in the airways of cystic fibrosis (CF) patients. Psl is an extracellular polysaccharide expressed by non-mucoid P. aeruginosa strains, which are believed to be initial colonizers. We hypothesized that Psl protects P. aeruginosa from host defences within the CF lung prior to their conversion to the mucoid phenotype. We discovered that serum opsonization significantly increased the production of reactive oxygen species (ROS) by neutrophils exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
208
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(216 citation statements)
references
References 54 publications
7
208
1
Order By: Relevance
“…Alginate has been shown to protect P. aeruginosa against human leukocyte killing (11), in addition to inhibiting pulmonary clearing and increasing bacterial load in a mucine lung infection model (19). Psl expression is also important for reduced phagocytosis (20). In line with this, increased immune evasion of ΔyfiR mutant strains has been reported, and it has been shown that disruption of pel and psl in a ΔyfiR mutant strain renders it as sensitive to phagocytosis by macrophages as the wild type (14).…”
Section: Discussionmentioning
confidence: 99%
“…Alginate has been shown to protect P. aeruginosa against human leukocyte killing (11), in addition to inhibiting pulmonary clearing and increasing bacterial load in a mucine lung infection model (19). Psl expression is also important for reduced phagocytosis (20). In line with this, increased immune evasion of ΔyfiR mutant strains has been reported, and it has been shown that disruption of pel and psl in a ΔyfiR mutant strain renders it as sensitive to phagocytosis by macrophages as the wild type (14).…”
Section: Discussionmentioning
confidence: 99%
“…Psl was shown contributing to biofilm production, tolerance to oxidizing agents and host defensive processes (Friedman and Kolter, 2004;Jackson et al, 2004;Mishra et al, 2012), that is, traits likely useful in insect interactions.…”
Section: Strain Selectionmentioning
confidence: 99%
“…Psl, a repeating pentasaccharide containing D-mannose, D-glucose and L-rhamnose [23], acts as 'molecular glue' to promote bacterial cell-cell and cell-surface interactions and it can form a fiber-like web to enmesh bacterial communities [6,7,17]. This exopolysaccharide also confers resistance of P. aeruginosa biofilms to antibiotics and phagocytic cells [9,[24][25][26]. In P. aeruginosa PAO1 (a common lab strain), Psl is more important than Pel for biofilm microcolony formation and antibiotic resistance [24].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important features of biofilms is extracellular polymeric substances consisting of mainly polysaccharides, proteins, and extracellular DNA (eDNA), which function as a matrix, or glue, holding biofilm cells together and protecting cells from antibiotics and shear forces in fluid environments [2,[6][7][8]. By forming a matrix-encased multicellular aggregate, cells can also escape engulfment by phagocytic cells within a mammalian host [9]. Hence, factors that disrupt biofilm matrix may disassemble or disperse biofilm, rendering biofilm bacteria sensitive to antibiotics and phagocytic cells.…”
Section: Introductionmentioning
confidence: 99%